Búsqueda de alimento y marcación de trillo por larvas de Brassolis sophorae (Lepidoptera: Nymphalidae) en condiciones naturales - Zanetti, Ronald (Universidad de Costa Rica, 1999)
The daily periodicity of foraging and trail marking behaviour of Brassolis sophorae larvae was studied between August, 1991 and July, 1992 in a cocoa plantation in Bahia, Brazil. Larvae, originating from eight different nests, were observed continually during the dark phase for 20 consecutive days. They foraged for a single period of time each day, starting at 17:56 h, and for a meam duration of 90 min and 36 s. Larvae mark trails with threads of silk while moving from the nest to the foraging site and viceversa